Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5586/aa.2015.034
|View full text |Cite
|
Sign up to set email alerts
|

Current glimpse of airborne allergenic pollen in Indian subcontinent

Abstract: Respiratory allergic diseases such as bronchial asthma, rhinitis, urticaria, atopic dermatitis have been steadily increasing all over the world, including India. Owing to its alarming trend, several aerobiological surveys have been undertaken in different parts of India to delineate the variety of pollen and spore load. In this review, we have reported the current state of aerobiological knowladge in India with particular reference to allergenic airborn pollen occurence in 2001–2015. Pollen have been found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Holoptelea integrifolia, an anemophilous species releases enormous pollens (estimated 7650 pollen grains per anther in a year); hence, the prevalence of H. integrifolia pollen (50-56%) is obvious in Delhi atmosphere. 37 Among grass pollens, Cynodon (3.05%) was the dominant allergen. 36 In a study from Allahabad in 2016, major pollens reported were Ricinus communis (28.33%), Amaranthus spinosus (28.33%), Parthenium hysterophorus (26.66%), Eucalyptus tereticornis (26.66%) and Cynodon dactylon (25%).…”
Section: Pollen Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…Holoptelea integrifolia, an anemophilous species releases enormous pollens (estimated 7650 pollen grains per anther in a year); hence, the prevalence of H. integrifolia pollen (50-56%) is obvious in Delhi atmosphere. 37 Among grass pollens, Cynodon (3.05%) was the dominant allergen. 36 In a study from Allahabad in 2016, major pollens reported were Ricinus communis (28.33%), Amaranthus spinosus (28.33%), Parthenium hysterophorus (26.66%), Eucalyptus tereticornis (26.66%) and Cynodon dactylon (25%).…”
Section: Pollen Allergymentioning
confidence: 99%
“…Among tree pollens, Holoptelia (5.01%) elicited highest sensitization. Holoptelea integrifolia , an anemophilous species releases enormous pollens (estimated 7650 pollen grains per anther in a year); hence, the prevalence of H. integrifolia pollen (50–56%) is obvious in Delhi atmosphere 37 . Among grass pollens, Cynodon (3.05%) was the dominant allergen 36 .…”
Section: Prevalence Of Allergies Against Different Sources Of Aero‐al...mentioning
confidence: 99%
“…Viruses are the smallest bio-aerosols present in the atmosphere (size approximately 0.003 μm) and are considered as major environmental risk factors to human, animal and plant species [92,93]. However, their occurrence in the atmosphere is mostly in association with suspended particles [94].…”
Section: Virusesmentioning
confidence: 99%
“…All the patients were diagnosed with a positive history of allergy against one or more common pollen allergen sources available in West Bengal and suffering from rhinitis, conjunctivitis, urticaria, oral allergy syndrome, or bronchial asthma, either alone or in combination. On the basis of the peak season for airborne pollen allergen sources in West Bengal [10], patients were categorized into seasonal (March -July) and perennial ones. In addition, 782 food-allergic (FA) patients were also recruited on the basis of a history of allergic reactions after consumption of an offending food.…”
Section: Study Populationmentioning
confidence: 99%